Influence of socio-economic factors on municipal solid waste generation - Kováčová, Alena (2010)
Diploma thesis examines the relationship between socio-demographic trends and municipal solid waste generation. It follows an increasing trend towards the integration of environmental, economic and social aspects to indicate the municipal solid waste generation at the present time. Not only gross domestic product, but also social indicators, household size and age structure have a significant impact on the amount of municipal solid waste. The topical aim of the thesis is to review the state of present knowledge regarding socio-demographic changes, analyse previously published models of municipal waste generation, identify socio-economic factors important for describing the amount of municipal waste at various levels in Czech Republic and observe broad scale of potential relationships. The observations and survey were made on two levels -- regional and city level. From the models obtained by working with various set of explanatory variables at regional level, one linear multivariate regression model with explanatorz power 90,20% was described in diploma thesis. It consists of one dependent variable -- municipal waste generation per household and five independent variables (net money income, household size, living costs per household per month, number of retired pensioners in household and households with net income below minimum subsistence). At city level, some parameters were just proved by correlation analysis, but they were not used as explanatory variables in regression analysis in order to obtain optimal model. Those used in regression analysis are number of inhabitants and number of people in main age groups. Regression index R2 indicates that this model explains 58,78% of the variability in total household waste generated in cities.